The Effectiveness of Acupressure Hegu LI 4 on Decreasing Labor Pain During Active Phase - Rafhani Rosyidah; Nurul Azizah; Widi Arti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Childbirth is a moment full of stress that causes pain, fear, and anxiety. Acupressure Hegu LI 4 is one of the techniques to reduce pain during labor. Objective of the study was to identify the difference in pain on first stage active phase of labor in acupressure Hegu LI 4 group and control group. Samples were obtained through consecutive sampling technique from parturient which fulfill inclusion criteria. The study was a quasy experiment design. Data analysis used mean and deviation standard for univariate analysis, Independent Sample T Test for bivariable analysis, and linier regretion for multivariable analysis. Mean of decrease of pain labor in aromatheraphy group was higher than control group. The mean decrease in pain score in the intervention group was 3.03 ± 0.669 while the mean reduction in pain in the control group was 2.07 ± 0.740. The average difference from the Independent Sample T Test obtained significant results with P values 0.001 and 95% C.I. -1,331 - (-0,602). Analysis of external variables that affect the decrease in labor pain scores is anxiety with P value = 0.020. The results of this study are expected to be the basis of studies in the field of midwifery, especially labor on effective methods to reduce labor pain in a non-pharmacological manner.